2023
DOI: 10.1371/journal.pone.0282304
|View full text |Cite
|
Sign up to set email alerts
|

Novel in-frame duplication variant characterization in late infantile metachromatic leukodystrophy using whole-exome sequencing and molecular dynamics simulation

Abstract: Metachromatic leukodystrophy (MLD) is a neurodegenerative lysosomal storage disease caused by a deficiency in the arylsulfatase A (ARSA). ARSA deficiency leads to sulfatide accumulation, which involves progressive demyelination. The profound impact of early diagnosis on MLD treatment options necessitates the development of new or updated analysis tools and approaches. In this study, to identify the genetic etiology in a proband from a consanguineous family with MLD presentation and low ARSA activity, we employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…For instance, MD simulations on WT and mutant ND4L-ND6 subunits revealed that the mutations limit the passage of water molecules leading to type 2 diabetes mellitus and cataracts [ 37 ]. Additionally, MD simulations on a mutation in the arylsulfatase A protein altered its structural and functional behavior, ultimately led to metachromatic leukodystrophy [ 38 ]. Identifying the effects of mutations on protein structure is critical for exploring disease pathogenesis at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, MD simulations on WT and mutant ND4L-ND6 subunits revealed that the mutations limit the passage of water molecules leading to type 2 diabetes mellitus and cataracts [ 37 ]. Additionally, MD simulations on a mutation in the arylsulfatase A protein altered its structural and functional behavior, ultimately led to metachromatic leukodystrophy [ 38 ]. Identifying the effects of mutations on protein structure is critical for exploring disease pathogenesis at the molecular level.…”
Section: Discussionmentioning
confidence: 99%